Organised crime and the efforts to combat it: a concern for public health - McKee Martin; Reynolds Lucy (BMC, 2010)
Abstract This paper considers the public health impacts of the income-generating activities of organised crime. These range from the traditional vice activities of running prostitution and supplying narcotics, to the newer growth areas of human trafficking in its various forms, from international supply of young people and children as sex workers through deceit, coercion or purchase from family, through to smuggling of migrants, forced labour and the theft of human tissues for transplant, and the sale of fake medications, foodstuffs and beverages, cigarettes and other counterfeit manufactures. It looks at the effect of globalisation on integrating supply chains from poorly-regulated and impoverished source regions through to their distant markets, often via disparate groups of organised criminals who have linked across their traditional territories for mutual benefit and enhanced profit, with both traditional and newly-created linkages between production, distribution and retail functions of cooperating criminal networks from different cultures. It discusses the interactions between criminals and the structures of the state which enable illegal and socially undesirable activities to proceed on a massive scale through corruption and subversion of regulatory mechanisms. It argues that conventional approaches to tackling organised crime often have deleterious consequences for public health, and calls for an evidence-based approach with a focus on outcomes rather than ideology.